2017
DOI: 10.1177/0013916517701795
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Emotions on the Acceptance of an Oil Drilling Project

Abstract: In 2014, the Canary Islands were exposed to a decision-making process for an oil drilling project 80 kilometers offshore. Whereas the national government was in favor of oil drilling, the local government was against it because of the environmental impact, and the effect on tourism and the coastal ecosystem. In this study, we analyze the reactions of the local community to this project by connecting beliefs, perceived benefits, perceived risk, procedural justice, negative emotions, and acceptance through a tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 69 publications
2
15
0
2
Order By: Relevance
“…The acceptance of different energy sources was positively related to utility, perceived benefits, and positive emotions, whereas it was negatively related to perceived risk and negative emotions. Previous research confirms the relationships found between psychosocial processes and acceptance of an oil drilling project [ 41 ]. Utility and perceived benefits were the variables most associated with acceptance of different energy sources.…”
Section: Resultssupporting
confidence: 83%
“…The acceptance of different energy sources was positively related to utility, perceived benefits, and positive emotions, whereas it was negatively related to perceived risk and negative emotions. Previous research confirms the relationships found between psychosocial processes and acceptance of an oil drilling project [ 41 ]. Utility and perceived benefits were the variables most associated with acceptance of different energy sources.…”
Section: Resultssupporting
confidence: 83%
“…The results of the surveys and the participatory process coincide with research carried out in the United States (Bishop 2014 ; Mukherjee and Rahman 2016 ), Europe (Ruiz et al 2018 ); China (Chen and Martens 2021 ) and Latin America (Diaz Mondragon et al 2021 ), which showed that coastal residents identify the environmental impacts of offshore exploitation as the main threat to the population. Among them, there is agreement on considerations about the contamination of the marine environment typical of activity maneuvers (Vidal Hernández et al 2012 ), the possibility of a serious disaster due to spills (Lilley and Firestone 2013 ; Bishop 2014 ; Vidal Hernández et al 2012 ; Mukherjee and Rahman 2016 ), and the health risks of local citizens (Michaud et al 2008 ) as the main impacts of the activity.…”
Section: Discussionsupporting
confidence: 74%
“…Numerous conflicts related to the form, place and activities that involve offshore drilling have been evidenced in different parts of the world (Haavik 2012 ; Mukherjee and Rahman 2016 ; Chen and Martens 2021 ). Studies have been conducted on the perception of risk to this activity in the United States (Bishop 2014 ; Mukherjee and Rahman 2016 ); Spain (Ruiz et al 2018 ) and China (Chen and Martens 2021 ), where society’s positions have been found in favor of offshore hydrocarbon exploitation (Gramling and Freudenburg 2006 ) and against (Bishop 2014 ; Mukherjee and Rahman 2016 ; Ruiz et al 2018 ). This have been related to proximity to exploitation sites (Chen and Martens 2021 ) or to moments after an environmental disaster caused by spills, such as the case of British Petroleum’s Deepwater Horizont 2 on the coasts of the Gulf of Mexico in 2010 (Bishop 2014 ; Lilley and Firestone 2013 ; Mukherjee and Rahman 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…While deep-sea environments are not attributed to the same symbolic value as the more charismatic Antarctica, this does not mean that social license would be granted automatically. As emotions and values towards activities that have the potential to cause environmental harm are likely to impact the magnitude of social resistance (Ruiz et al, 2018), public attitudes towards deep-sea activities may be different. However, even if the public outcry would take a different form, it is unlikely that DSM activities could proceed without considering public concerns.…”
Section: Societal Engagement In Deep-sea Governance and Social Licencementioning
confidence: 99%